Toxicity and protein composition of venoms of Hottentotta saulcyi, Hottentotta schach and Androctonus crassicauda, three scorpion species collected in Iran - Ani Boghozian (Wiley, 2021)
Abstract Background Scorpion stings comprise a serious problem throughout the globe, especially in regions where they are more frequent. Despite a recent upsurge of interest in scorpion venoms by various research groups, there remain many challenges. Objective Therefore, in this study, we aimed to study the toxicity and protein composition of venoms of Hottentotta saulcyi, Hottentotta schach and Androctonus crassicauda, three scorpion species collected in Iran. Materials and Methods Scorpion species were collected from Esfahan farm scorpion company and maintained in the laboratory in containers that mimic their natural habitat. Venom was extracted from A. crassicauda, H. schach and H. saulcyi by electrical stimulation of 8 and 10 V. The toxicity of each venom was established by using four groups of male Swiss albino mice aged 2 months (weighting 18–20 g) for testing each dose of venom. One group was used as a control. Venom was injected into mice by subcutaneous route. Then, animals were monitored for 24 h and LD50 was estimated by the graphic method of Miller and Tainter. Thus, high‐performance liquid chromatography–tandem mass spectrometry (HPLC–MS/MS) method was used to determine amino acids in the venom, and protein concentrations were determined by the Biuret method. Results LD50 of scorpion venoms by subcutaneous route was found to be 1.70 mg/kg b.w (A. crassicauda), 1.47 mg/kg b.w (H. saulcyi) and 0.85 mg/kg b.w (H. schach). A. crassicauda, H. saulcyi and H. schach contain 26, 30, and 31 amino acids, respectively. A. crassicauda contains low concentrations of alpha‐aminoadipic acid, beta‐aminoisobutyric acid, beta‐alanine and citrulline. H. saulcyi contains a concentration of hydroxylysine, whereas H. schach has no such concentration. A. crassicauda also had the highest levels of tyrosine and threonine. Only A. crassicauda venom contains a low proportion of proteins (14.80%) compared with those of H. schach (16.26%) and H. saulcyi (16.20%). Albumin content in the venoms was 11.7% (H. saulcyi), 5.4% (H. schach) and 4.4% (A. crassicauda). Conclusion Scorpions venoms have a variable toxicity and an interesting composition in amino acids and proteins. Work on the development of anti‐venom is fundamental.